Max Weber in politics and social thought from charisma to canonization - Derman, Joshua 1977- (Cambridge Cambridge University Press, 2012)
"Max Weber is widely regarded as one of the foundational thinkers of the twentieth century. But how did this reclusive German scholar manage to leave such an indelible mark on modern political and social thought? Max Weber in Politics and Social Thought is the first comprehensive account of Weber's wide-ranging impact on both German and American intellectuals. Drawing on a wide range of sources, Joshua Derman illuminates what Weber meant to contemporaries in the Weimar Republic and Nazi Germany and analyzes why they reached for his concepts to articulate such widely divergent understandings of modern life. It also accounts for the transformations that Weber's concepts underwent at the hands of e;migre; and American scholars, and in doing so, elucidates one of the major intellectual movements of the mid-twentieth century: the transatlantic migration of German thought"--
Machine generated contents note: Introduction; 1. Max Weber and his circles; 2. Value freedom and polytheism; 3. The meaning of modern capitalism; 4. Skepticism and faith; 5. Max Weber's sociologies; 6. Charismatic rulership; Conclusion.
Includes bibliographical references and index.
Keywords: Weber, Max, -- 1864-1920 -- Political and social views; Weber, Max, -- 1864-1920 -- Influence; Political science -- Philosophy -- History -- 20th century; Political science -- United States -- Philosophy -- History -- 20th century; Political science -- Germany -- Philosophy -- History -- 20th century; Political science / History & Theory